Efektivitas Edukasi Perilaku Hidup Bersih dan Sehat (PHBS) SD Negeri Wamsoba Kecamatan Namrole Buru Selatan - Samsudin, Arfifa; Rettob, Utari Permata Putri; Salakory, Hans S. M.; Matulessy, Febby S. (Universitas Pahlawan Tuanku Tambusai, 2026)
Limited sanitation infrastructure in underdeveloped regions serves as a primary barrier to implementing Clean and Healthy Living Behavior (PHBS). SD NegeriWamsoba in Namrole, South Buru, lacks access to clean water and latrines, thereby hindering Handwashing with Soap (CTPS) practices. This activity aims to enhance student competence through education and demonstration. Employing a one-group pre-test/post-test quasi-experimental design on 20 students, effectiveness was analyzed using N-Gain. Results indicated a significant increase in knowledge from 42.1% to 85.3% (high category) and CTPS skills from 16.1% to 69.1% (medium category). These findings demonstrate that while education effectively improves cognitive understanding, motor behavior changes remain constrained by inadequate facilities. Consequently, educational interventions must be accompanied by the provision of sanitation facilities to ensure PHBS sustainability.